Pelatihan Pidato untuk Anak-Anak dalam Menumbuhkan Kepercayaan Diri di Desa Mangun Jaya - Inayah, Siti; Zulfa, Fitria; Karyono; Farihin, Ahmad (CV Global Research Publication, 2026)
This Community Service Program (PKM) aimed to improve public speaking skills and self-confidence among children in Mangun Jaya Village through speech training. The program was initiated due to children’s lack of courage and limited experience in public speaking caused by inadequate facilities and guidance. The research employed a descriptive qualitative method with a Participatory Action Research (PAR) approach, involving 30 children aged 9–13. Data were collected through observation, interviews, and documentation. The training was conducted over seven days, covering the introduction of speech, basic techniques, script reading practice, simulations, feedback sessions, and a speech contest. The results indicated significant improvement in the children’s courage, intonation, articulation, eye contact, and self-confidence. Support from parents and local authorities also contributed to the program’s success. Despite limitations in time and facilities, the program proved effective in addressing children’s low public speaking skills. In the future, the program can be developed further by adding materials such as debates, presentations, or drama to broaden communication skills.